Increases of calcium and phosphorus in the uterine arteries with aging - Setsuko Tohno (2018)
To elucidate compositional changes of the uterine artery with aging, the authors investigated age-related changes of elements in the uterine arteries. After ordinary dissection by medical students at Nara Medical University was finished, the uterine arteries were resected from the subjects. The element content of the uterine arteries was analyzed by inductively coupled plasma-atomic emission spectrometry. The subjects ranged in age from 58 to 99 yr (average age ≤ 82.7 ± 10.1 yr). It was found that the Ca, P, and Na contents increased progressively in the uterine arteries with aging. A significant accumulation of Ca and P in the uterine arteries was found in the sixties and increased markedly in the eighties. It should be noted that as far as the arteries in those over 70 yr of age, the extent of accumulation of Ca and P was the highest in the uterine arteries within the limits of the arteries analyzed by us. Regarding the relationships among elements, significant direct correlations were found among the contents of Ca, P, Mg, Zn, and Na. As Ca increased in the uterine arteries, P, Mg, Zn, and Na increased simultaneously in the arteries. © Copyright 2007 by Humana Press Inc. All rights of any nature, whatsoever, reserved.